2019
DOI: 10.3389/fnbeh.2019.00166
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Hatching Time Predict Alcohol Response in Zebrafish

Abstract: There are significant individual differences in response to alcohol: some people seem to exhibit higher alcohol sensitivity, while others are more resistant. These differences are related to alcohol metabolism, inherited traits, environmental/social pressure, personal habits and other indeterminate causes. In order to test how individual differences in hatching time are related to behavioral response to different alcohol concentrations, we separated zebrafish larvae into two categories according to egg emergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 75 publications
(108 reference statements)
1
7
0
Order By: Relevance
“…High‐dose (750 and 1,000 mg/L) applications appeared to have neurotoxic effects on vacuole formation in the brain tissues of the 96th‐hour larvae. Similar to our findings, other studies have reported changes in behavior and movements in embryos, larvae, and adults, and differences in hatching rates in embryos due to the neurotoxic effects of acute and chronic alcohol administration in Zebrafish (Chatterjee et al 2014; Ramlan et al 2017; Leite‐Ferreira et al 2019; Zindler et al 2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…High‐dose (750 and 1,000 mg/L) applications appeared to have neurotoxic effects on vacuole formation in the brain tissues of the 96th‐hour larvae. Similar to our findings, other studies have reported changes in behavior and movements in embryos, larvae, and adults, and differences in hatching rates in embryos due to the neurotoxic effects of acute and chronic alcohol administration in Zebrafish (Chatterjee et al 2014; Ramlan et al 2017; Leite‐Ferreira et al 2019; Zindler et al 2019).…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that high doses of n‐butanol reduce the release of the enzyme choriolysis secreted by these cells via reducing the incubation gland cells (Muller et al 2015; De la Paz et al 2017; Ferdous et al 2017; Sizochenko et al 2017). In our study, the reason for n‐butanol to decrease hatching at 42 h and cause a complete halt at 72, 96, and 120 h in the high‐dose application groups (750, 1,000; and 1,250 mg/L) depends on the neurotoxic effect of n‐butanol, and it can be interpreted as affecting motor activity in embryos (Chatterjee et al 2014; Ramlan et al 2017; Leite‐Ferreira et al 2019; Zindler et al 2019).…”
Section: Discussionmentioning
confidence: 72%
“…As individual coping styles also vary in the responsiveness of these very same physiological systems and behavioural read-outs (Egan et al 2009;Tran et al 2016b;Rey et al 2013;Tudorache et al 2018), it should be no surprise to find interactive effects through direct neurophysiological processes (c.f. Araujo-Silva et al 2018Leite-Ferreira et al 2019).…”
Section: Activity Level Dependent Ethanol Impactmentioning
confidence: 99%
“…Zebrafish, besides being a suitable model for alcohol effects, are also suitable for studies on intra-specific, mechanistic variation and potential methodological issues with inter-individual variation, as distinct behavioural and physiological phenotypes are well-established (Egan et al 2009;Oswald et al 2012;Tran and Gerlai 2013a;Tudorache et al 2013;Roy and Bhat 2018). Responsiveness to a specific alcohol concentration may not only vary among different populations of zebrafish (Dlugos and Rabin 2003;Gerlai et al 2009), but also among different individuals of the same population (Dlugos et al 2011;Leite-Ferreira et al 2019;Wong et al 2019;Goodman and Wong 2020). Araujo-Silva et al (2018), for example, showed that bold individuals were not much affected in shoaling and explorative behaviour, but that shy individuals, who tend to shoal more and explore less, became also more explorative with exposure to 0.1 and 0.5% ethyl alcohol (also see Araujo-Silva et al (2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation